Immature Platelet Fraction as A Potential Marker To Differentiate Types of Acute Coronary Syndrome - Endah Indriastuti; Yetti Hernaningsih; Yulia Nadar Indrasari; Andrianto Andrianto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Acute Coronary Syndrome (ACS) includes ST-Elevation Myocardial Infarction (STEMI), non-ST Elevation Myocardial Infarction (NSTEMI), and Unstable Angina (UA). Platelet plays an essential role in ACS pathogenesis. Immature Platelet Fraction (IPF) and platelet indices can predict platelet activations. Platelet indices consist of platelet count, Mean Platelet Volume (MPV), Platelet Distribution Width (PDW), plateletcrit (Pct). This study aimed to analyze the differences of IPF and platelet indices among ACS patients. This study was an observational analytical cross-sectional study conducted in Dr. Soetomo Hospital during May-September 2019. The subjects consisted of 30-STEMI, 25-NSTEMI, and 24-UA patients. The EDTA-samples were measured for platelet indices and IPF using Sysmex XN-1000. The differences between IPF and platelet indices among STEMI, NSTEMI, and UA patients were analyzed using Kruskal-Wallis and Mann-Whitney test. The IPF values were significantly higher in STEMI patients than NSTEMI and UA patients. The IPF values of NSTEMI patients were higher than UA patients. The MPV, PDW, and P-LCR were significantly higher in STEMI and NSTEMI compared to UA. The MPV, PDW, and P-LCR values of NSTEMI patients were significantly higher than UA patients. The significant differences between STEMI and NSTEMI toward UA might be caused by the more severe thrombotic conditions in myocardial infarction patients than UA. The IPF values were significantly different among each type of ACS patients gave an opportunity using this parameter to differentiate the ACS types. The MPV, PDW, and P-LCR were significantly higher in myocardial infarction patients than UA patients, which also allowed them to use those parameters to differentiate both conditions.